Villa-Lobos’s Fourth Symphony: the victory, the defeat, and the comeback (Orfeu, 2020)
The purpose of this paper is to present an analysis of Symphony No. 4 (The Victory) by Heitor Villa-Lobos (1887-1959), from formal and narrative perspective. The work was composed in 1919 to celebrate the end of the First World War. Its premiere was planned to a concert in honor of the king and queen of Belgium, who visited Brazil in 1920.Symphony No. 4 is based on a text written by Luís Gastão d’Escragnolle Dória (1869-1948), so it was originally a symphonic poem. The literary narrative is covered by another, of a musical character, structured in a cyclic form according to the method of Vincent d’Indy. The analysis search for points of closure and detachment among literary and musical narratives, according to theories of narrativity advanced by Eero Tarasti (1994) and Byron Almén (2008), as well musical topic analysis, after Leonard Ratner (1980) Wye Allanbrook (1983), and Raymond Monelle (2000, 2006) among others. My goal is to interpret the musically meaningful aspects resulting from intertextuality between music and text.
Keywords: Villa-Lobos; Symphony; Narrativity; Topics theory; Musical analysis